Hours of work and on-call weeks preferences of Canadian midwives: relationships with intention to stay in the profession - Isik U. Zeytinoglu; Firat K. Sayin; Elena Neiterman; Farimah HakemZadeh; Johanna Geraci; Jennifer Plenderleith; Derek Lobb (BMC, 2022)
Abstract Background Midwives have long workdays and work many weeks on call. There is a concern that these extended work schedules can negatively affect their intention to stay in the profession. Purpose This study provides evidence on Canadian midwives' preferences for and experiences with policies and guidelines which limit the hours of work and weeks per year preferred to be on call, and examines the relationship between preferences and midwives' intention to stay in the profession. Methods Data come from our 2018 pan-Canadian survey of midwives. Descriptive statistics of 720 midwives' preferences and experiences are provided. In the correlations followed by the OLS regressions, 596 midwives' data are used to test the associations between preferences and intention to stay in the profession. STATA (version 15) is used. A thematic analysis of 274 midwives' responses to the open-ended survey question is conducted to give voice to midwives on what can be done for retention. Results Three quarters of the 720 respondents prefer policies and guidelines to limit hours of work in a 24-hour period, though less than half have policies and guidelines on hours of work. More than half prefer to have fewer on-call weeks or never to be on call, less than a third prefer same number of on-call weeks, and only 2% prefer more weeks to be on call. Midwives are currently working on average 33 weeks per year on call. OLS regression analysis shows that 'met preference' for hours of work and on-call weeks are positively associated with intention to stay. In responding to the open-ended survey question, midwives recommend limiting the consecutive hours of work and on-call weeks to manageable hours and weeks to retain them in the profession. Conclusion Midwives whose preferences are met are the ones intending to stay in the profession. There is, however, a large number of midwives with 'unmet needs' preferring to have policies and guidelines to limit the hours but do not have that currently, and would like to work fewer weeks on call than currently. These are the midwives who are not intending to stay in the profession.